The Influence of Company Size, Accounting Conservatism, Free Cash Flow on Profit Management with Managerial Ownership as Moderation - Fitri Hermalia Putri; Eka Kusuma Dewi (CV. Rayyan Dwi Bharata, 2024)
This study aims to empirically prove the effect of company size, accounting conservatism and free cash flow on earning management with managerial ownership as a moderation in empirical studies of consumer cyclical sector companies listed on the IDX in 2018 – 2022. In this study, the company size is proxied by total assets. Then accounting conservatism is proxied by operating accruals. And the free cash flow is proxied by cash flow difference. Then managerial ownership is proxied by proportion of company shares. The model used to see the potential for earning management is discretionary accruals. This type of research is quantitative research using associative methods. The number of research samples was determined using a purposive sampling technique, so that a sample of 14 companies could be produced with a total of 70 observational data. The data used in this study was processed using Microsoft Office Excel and E-views 12. The results of the statistical F test show that the model can explain that company size, accounting conservatism, free cash flow have a simultaneous effect on earning management. The results of statistical test T on the variabel company size has no influence on earning management. Accounting conservatism have a negative effect on earning management. And free cash flow has no influence on earning management. The results of the analysis of the moderation of managerial ownership variables cannot moderate the shield between company size, accounting conservatism, and free cash flow to earning management